Hubungan Dukungan Keluarga Dengan Tingkat Stres Depresi Kecemasan Pada Mahasiswa Keperawatan Di Universitas Advent Indonesia - Sihombing, Gebryela Raquelina; Perangin-angin, Mori (NUTRIX, 2025)
Final-year students are prone to stress, depression, and anxiety due to academic demands. Family support is believed to play an important role in helping students cope with academic pressure. This study aims to determine the relationship between family support and levels of stress, depression, and anxiety among third-year undergraduate nursing students at Advent University Indonesia. The research design used a descriptive quantitative correlation approach with a cross-sectional method. The sample size was 65 respondents selected using total sampling, with data collection through a questionnaire that had been tested for validity and reliability. Data analysis used the Pearson Product Moment correlation test. The results showed that the majority of students (90.8%) received good family support. The highest level of stress was in the normal category (40%), depression in the moderate category (36.9%), and anxiety in the very severe category (32.3%). Statistical test results showed a significant relationship between family support and stress depression and anxiety (p = 0.028 < 0.05). This study concluded that family support plays a protective role in students' mental health, thereby reducing the risk of psychological disorders. It is recommended that students be more open with their families, educational institutions optimize counseling services, and future studies consider other variables such as peer support and coping strategies. Mahasiswa tingkat akhir rentan mengalami stres, depresi, dan kecemasan akibat tuntutan akademik. Dukungan keluarga diyakini berperan penting dalam membantu mahasiswa menghadapi tekanan akademik. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan keluarga dengan tingkat stres, depresi, dan kecemasan pada mahasiswa Keperawatan S1 tingkat III di Universitas Advent Indonesia. Desain penelitian menggunakan pendekatan kuantitatif deskriptif korelasi dengan metode cross-sectional. Besar Sampel berjumlah 65 responden yang dipilih menggunakan total sampling, dengan pengumpulan data melalui kuesioner yang telah diuji validitas dan reliabilitas. Analisis data menggunakan uji korelasi Pearson Product Moment. Hasil penelitian menunjukkan bahwa mayoritas mahasiswa (90,8%) memperoleh dukungan keluarga yang baik. Tingkat stres terbanyak berada pada kategori normal (40%), depresi pada kategori sedang (36,9%), dan kecemasan pada kategori sangat parah (32,3%). Hasil uji statistik menunjukkan adanya hubungan signifikan antara dukungan keluarga dengan stres depresi dan kecemasan (p = 0,028 < 0,05). Penelitian ini menyimpulkan bahwa dukungan keluarga memiliki peran protektif terhadap kesehatan mental mahasiswa, sehingga dapat menurunkan risiko gangguan psikologis. Disarankan agar mahasiswa lebih terbuka kepada keluarga, institusi pendidikan mengoptimalkan layanan konseling, serta penelitian selanjutnya mempertimbangkan variabel lain seperti dukungan teman sebaya dan strategi koping.